Use of heart rate variability in biomedical training control - Jaime Gallo-Villegas (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Physical training generates physiological changes throughout the body in order to improve physical performance. Nevertheless, the response to physical training is heterogeneous due to factors related to training and recovery, and individual and contextual factors. Heart Rate Variability (HRV) is an indicator of the sympathetic-vagal balance that has been used for an efficient prescription of exercise in the general population and for the control of training in high performance athletes. In this article, we review the available methods of HRV analysis (time domain, frequency domain and nonlinear dynamics) and the current recommendations for its practical application.